(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2023)
This is a 61-year-old male patient who was admitted through the emergency service. In the anamnesis he presents a sedentary lifestyle and overweight as the only risk factors and no previous cardiovascular history. He is admitted with a history of typical angina lasting two days. The first electrocardiogram recorded shows negative, deep and symmetrical T waves in the precordial leads. This condition meets the clinical and electrocardiographic criteria of Wellens syndrome, whose recognition and appropriate intervention would prevent a potential extensive anterior myocardial infarction.